Deep MOS spectroscopy of NGC1316 globular clusters - Sesto, Leandro Alberto (2017)
The giant elliptical galaxy NGC1316 is the brightest galaxy in the Fornax cluster, and displays a number of morphological features that might be interpreted as an intermediate age merger remanent (~3 Gyr). Based on the idea that globular clusters systems (GCS) constitute genuine tracers of the formation and evolution of their host galaxies, we conducted a spectroscopic study of approximately 40 globular clusters (GCs) candidates associated with this interesting galaxy. We determined ages, metallicities, and α-element abundances for each GC present in the sample, through the measurement of different Lick indices and their subsequent comparison with simple stellar populations models (SSPs).